The Cambridge Companion to Autobiography (Cambridge Companions to Literature, 2014)
"The Cambridge Companion to Autobiography offers a historical overview of the genre from the foundational works of Augustine, Montaigne, and Rousseau through the great autobiographies of the Romantic, Victorian, and modern eras. Seventeen essays from distinguished scholars and critics explore the diverse forms, audiences, styles, and motives of life writings traditionally classified under the rubric of autobiography. Chapters are arranged in chronological order and are grouped to reflect changing views of the psychological status, representative character, and moral authority of the autobiographical text. The volume closes with a group portrait of late-modernist and contemporary autobiographies that, by blurring the dividing line between fiction and non-fiction, expand our understanding of the genre. Accessibly written and comprehensive in scope, the volume will appeal especially to students and teachers of non-fiction narrative, creative writing, and literature more broadly"--